ANALISIS KENAIKAN PLANT HEAT RATE PLTU SEBELUM PERBAIKAN BERKALA TERHADAP KONDISI TESTING KOMISIONING (Studi Kasus : PLTU XX) - Komarudin Komarudin; Andrian Saputro; Erfiana Wahyuningsih (Bina Teknika, 2020)
Steam power plant is a power plant which use coal as fuel to heating the water into superheated steam. The standard of efficient or not for a power plant can be seen from the value of plant heat rate. Plant heat rate is amount of energy required to generate one kWh electricity. The smallest of that is the best power plant. In general, the value of plant heat rate has increased than commisioning test after the power plant operated continously. The method used in the calculation of the steam power plant is energy balance method. Energy balance calculation method used by the standard of the American Society of Engineers Mechanichal Performance Test Code (ASME PTC). The value of plant heat rate is influenced by the value of turbine heat rate and boiler efficiency from steam power plant. Turbine heat rate is the required energy turbines obtained from heat transfer process to generate one kWh electricity, while boiler efficiency is an indicator from boiler performance of steam power plant by comparing the outputs and inputs. After calculation of plant heat rate at actual condition, the value of plant heat rate has increased than commisioning. The increrase of plant heat rate value is due to more losses which result degradation performance on the main components of the unis, such as : turbine, boiler, air heater and condenser. Therefore necessary corrective maintenance when first year inspection, so that the steam power plant can be re-optimal performance as at commisioning test.